2003
DOI: 10.1002/mus.10487
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications of chronic neuromuscular diseases and their management

Abstract: Chronic neuromuscular diseases may affect all major respiratory muscles groups including inspiratory, expiratory, and bulbar, and respiratory complications are the major cause of morbidity and mortality. Untreated, many of these diseases lead inexorably to hypercapnic respiratory failure, precipitated in some cases by chronic aspiration and secretion retention or pneumonia, related to impairment of cough and swallowing mechanisms. Many measures are helpful including inhibition of salivation, cough-assist techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
193
1
18

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(215 citation statements)
references
References 184 publications
(341 reference statements)
3
193
1
18
Order By: Relevance
“…6 In our Case 1, the diagnosis of MG may have been delayed because at least part of the initial symptoms of fatigability and shortness of breath attributed to FSHD were probably due to untreated MG. Although rare (Ͻ1%), respiratory dysfunction alone may be the presenting symptom of MG. 4 Although atypical phenotypes, such as progressive external ophthalmoplegia, have been described in one family with FSHD, 3 the diagnosis of FSHD was questioned when ptosis and severe bulbar dysfunction developed.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…6 In our Case 1, the diagnosis of MG may have been delayed because at least part of the initial symptoms of fatigability and shortness of breath attributed to FSHD were probably due to untreated MG. Although rare (Ͻ1%), respiratory dysfunction alone may be the presenting symptom of MG. 4 Although atypical phenotypes, such as progressive external ophthalmoplegia, have been described in one family with FSHD, 3 the diagnosis of FSHD was questioned when ptosis and severe bulbar dysfunction developed.…”
mentioning
confidence: 72%
“…I read with interest the review by Perrin et al 6 and found it comprehensive except for one important omission. The authors failed to note "air stacking" or the importance of maximal lung insufflations prior to attempts at manually assisted coughing.…”
Section: Air Stacking For Cough Assistancementioning
confidence: 99%
“…Bilateral diyafragma paralizisinde yatar pozisyonda VC'deki azalma %50'den fazla olabilir. Kas güçsüzlüğü olan hastalarda TLC ve IC azalırken FRC değişkenlik gösterir, azalabilir veya artabilir (29,36).…”
Section: Restri̇kti̇f Hastaliklarda Akci̇ğer Volümleri̇unclassified
“…Diseases within NMD can be divided into diseases of the central nervous system (cerebral cortex, brainstem, basal ganglia and spinal cord) and in disease of the peripheral nervous system (motor nerves, neuromuscular junction and myopathies). 30,31 For patients with NMD, one of the main causes of morbidity and mortality is due to complications of respiratory muscle dysfunction. 32 .…”
Section: Pulmonary Function In People With Neuromuscular Disorders (Nmd)mentioning
confidence: 99%